Polymer Brushes: Novel Surfaces for Biomedical Applications - Ahmed Al-Ani; Emad Yousif (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Polymer brushes play an important role in surface modification techniques to improve the biocompatibility of modified surfaces inside the human body for different biological and biomedical applications. This modification gives the ability to control biointerfacial interactions such as cell attachment, protein adsorption, and bacterial biofilm formation. Surface modification with polymer layers can be utilized to alter the surface properties, including biocompatibility, antifouling ability, corrosion resistance, and wettability, and it can be achieved by immobilization or spraying of polymers from solution. Also, it is easy to graft polymers with reactive end groups onto surfaces, leading to the formation of polymer brushes at high density, which have specific features, such as chemical robustness, tunable mechanical properties and the flexibility to use polymers of different chemistry or the introduction of bifunctional polymers for specific immobilization of other molecules, especially proteins and enzymes. The specific properties of polymer brushes make them ideal candidates to be used in the biomedical field. For example, polymer brushes can be synthesised on different substrates, particularly metallic and non-metallic surfaces. The technique is flexible in nature, which enables the terminal functional groups of the attached chains to be tailored with ligands for enhancing cell adhesion and proliferation while at the same time preventing non-specific adsorption of other proteins. In addition, Due to interfacial attachment to biomaterials, polymer brushes can be designed to encourage cells to attach and grow through simple modification and conjugation processes, finding applications in drug delivery, implants and tissue engineering Polymer brushes play an important role in surface modification techniques to improve the biocompatibility of modified surfaces inside the human body for different biological and biomedical applications. This modification gives the ability to control biointerfacial interactions, such as cell attachment, protein adsorption, and bacterial biofilm formation. Surface modification with polymer layers can be utilised to alter the surface properties, including biocompatibility, antifouling ability, corrosion resistance, and wettability, and it can be achieved by immobilisation or spraying of polymers from solution. Also, it is easy to graft polymers with reactive end groups onto surfaces, leading to the formation of polymer brushes at high density, which have specific features, such as chemical robustness, tunable mechanical properties and the flexibility to use polymers of different chemistry or the introduction of bifunctional polymers for specific immobilisation of other molecules, especially proteins and enzymes. The specific properties of polymer brushes make them ideal candidates to be used in the biomedical field. For example, polymer brushes can be synthesised on different substrates, particularly metallic and non-metallic surfaces. The technique is flexible, which enables the terminal functional groups of the attached chains to be tailored with ligands for enhancing cell adhesion and proliferation while at the same time preventing non-specific adsorption of other proteins. In addition, due to interfacial attachment to biomaterials, polymer brushes can be designed to encourage cells to attach and grow through simple modification and conjugation processes, finding applications in drug delivery, implants and tissue engineering.